Pelatihan Inovasi Produk Pangan Berbahan Baku Singkong di Kecamatan Lembang Kabupaten Bandung Barat - Tri Cahyanto; Ateng Supriyatna; Ucu Julita; Astuti Kusumorini; Anggita Rahmi Hafsari; Yani Suryani; Ana Widiana; Ida Kinasih; Mohamad Agus Salim (Universitas Muhammadiyah Pringsewu, 2018)
Cassava is one of the main local agricultural produced in Lembang sub district, West Java. However, this big potential is still not used optimally because of lack of skill and knowledge of local resident to produce higher economic product made from cassava. Most of resident only use it as raw material to produce traditional foods with relatively low economic value. One of alternative processing of cassava that can enhance higher profit is producing modified cassava flour, best known as mocaf. This training aims to give resident information and skill about mocaf and its process, also offer alternative use of cassava to get higher profit. The target of this training was several housewives joined in Syariah Micro Finance group living in Lembang sub district. This training was held by two sections, the first section was giving general information about mocaf and the second section was demonstrating and practicing how to make mocaf from fresh cassava and some foods made from mocaf. The result shows that audiences gave very good responses to the training. Making mocaf from cassava was new information for them. All audiences were able to practice how to make mocaf successfully. In conclusion, the processing cassava to mocaf could be an alternative and potential business for local resident in Lembang sub district. Keywords: cassava, food, mocaf, product,